The timing and departure rate of larvae of the warble fly Hypoderma (= Oedemagena) tarandi (L.) and the nose bot fly Cephenemyia trompe (Modeer) (Diptera: Oestridae) from reindeer - Nilssen, Arne C.; Haugerud, Rolf E. (Rangifer, 1994)
The emergence of larvae of the reindeer warble fly Hypoderma (= Oedemagena) tarandi (L.) (n = 2205) from 4, 9, 3, 6 and 5 Norwegian semi-domestic reindeer yearlings (Rangifer tarandus tarandus (L.)) was registered in 1988, 1989, 1990, 1991 and 1992, respectively. Larvae of the reindeer nose bot fly Cephenemyia trompe (Moder) (n = 261) were recorded during the years 1990, 1991 and 1992 from the same reindeer. A collection cape technique (only H. tarandi) and a grating technique (both species) were used. In both species, dropping started around 20 Apr and ended 20 June. Peak emergence occurred from 10 May - 10 June, and was usually bimodal. The temperature during the larvae departure period had a slight effect (significant only in 1991) on the dropping rate of H. tarandi larvae, and temperature during infection in the preceding summer is therefore supposed to explain the uneven dropping rate. This appeared to be due to the occurrence of successive periods of infection caused by separate periods of weather that were favourable for mass attacks by the flies. As a result, the temporal pattern of maturation of larvae was divided into distinct pulses. Departure time of the larvae in relation to spring migration of the reindeer influences infection levels. Applied possibilities for biological control by separating the reindeer from the dropping sites are discussed.